Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi dalam Film Pendek “Kemenangan Sejati” - Hesty Adila Putri; Yunita Zahrotul Khoeriyah; Ghea Novia Suci Savitri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
As an audiovisual medium, film plays a very important role in conveying educational and moral messages. Through dialogue between characters, films not only tell stories but also depict real-life social interactions in which language is used to influence the thoughts, emotions, and behaviors of others. The purpose of this study is to describe the speech acts contained in the short film “Kemenangan Sejati.” The method used in this study is qualitative descriptive analysis employing the observe-and-record technique. The data source consists of dialogues between characters in the film “Kemenangan Sejati,” with a focus on locutionary, illocutionary, and perlocutionary speech acts. The results of this study indicate that the short film “Kemenangan Sejati” contains locutionary, illocutionary, and perlocutionary speech acts. The types of illocutionary acts identified include directive, assertive, expressive, and commissive. The perlocutionary effects include making the addressee curious, causing the addressee to carry out the speaker’s instructions, evoking feelings of tenderness or other emotions, and so on.